KEBIJAKAN PEMERINTAH TERHADAP PELESTARIAN HUTAN MANGROVE DI KECAMATAN TEBING TINGGI KABUPATEN BENGKALIS - Fitri, Rahmah Yati; Anwar, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Mangrove deforestation in Riau province, especially in the District of High Cliff from 2005 until 2013 every year or penguranga damaged mangrove forest area of 1.35% per year (Department of Fisheries Riau, 2014). It can be seen from some of the phenomena which states that: mangrove forest cover in the district of High Cliff Bengkalis decreases. According to the report Riau Provincial Forestry Office (2014), estimated the damage rate will continue to grow each year. This is due to the internal and external pressures on the mangrove forests, the lack of regulations or policies Bengkalis area of the Regional Forest Service Bengkalis itself to the protection of mangrove forests in Bengkalis to date, geophysical changes in recent decades have encouraged onset of abrasion in areas that threaten Bengkalis mangrove forests. Reduced extensive mangrove provide a very important influence for the community and also life, especially in Bengkalis ecosystem, where the coastal areas until the last decade continues to experience a serious abrasion, especially in the northern part of the island. Abrasion that occurred on this island every year, reaching 5-10 m in length abrasion-hit areas reaching 100 km more.The purpose of this paper is to analyze the policy conducted by the Department of Forestry and Plantation Bengkalis safeguard Mangrove forest in the district of High Cliff Bengkalis.The result showed that the responses of informants according to the interview, observation and documentation available from the Forest Service concluded that Bengkalis not maximal preservation of mangrove forests in the District High Cliff Bengkalis due to the low resources (resources) in particular Bengkalis Forest Service , people in the District High Cliff and also entrepreneurs who average panglong not understand forestry legislation, and the risk of sanctions imposed on perpetrators of mangrove forest destruction. Besides the lack of government policies and the Forest Service Bengkalis Bengkalis towards conservation of mangrove forests lead to many critical land and also the ineffectiveness of mangrove reforestation on forest land. Keyword : Communcation, Resources, Disposition, Bureaucratic, Structure